Sistem Informasi Surat Masuk Pada Pengelolaan Rantai Suplai Satuan Kerja Khusus Migas - mulyati, Mulyati; Sany, Nasril; Kurniawan, Muhamad (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2020)
The correspondence system is one of the factors that influence the management of letters in the SKK Migas Supply Chain Management Division, so it is very necessary to manage the letter better, faster, and easily. This Information System can reduce so much use of time in archiving letters and dispositions, reduce paper use, reduce the possibility of errors in recording, speed up the search process of the letter, facilitate the control of disposition of letters, and easy to use. This system also eases the process of data communication between sections and makes reports that are always updated and can be seen in the monthly and annually reports. The Incoming Mail Information System is created using tools such as PHPMyAdmin, MySQL as a database and Xampp as the server.